Radioactive Waste Classification, Management and Environment - Hosan, Md. Iqbal (Engineering International, 2017)
Radioactive waste comes from the nuclear power production facilities; defense-related weapon activities, medical/hospitals use radioisotopes and research activities has a dreadful crisis for management and protecting the environment to be safe to the present and future generations. In this study different types of waste are classified according to international standards, the source of waste is identified around the world and Bangladesh, and waste disposal plan in the world and Bangladesh are analyzed. Although Bangladesh has excellent facilities for the management of present radioactive waste its need improvement for the final disposal of the present and future radioactive waste arise from the country’s first nuclear power plant.
Keywords: Radioactive Waste; Waste Classification; Geological Disposal; Transmutation; Regulations; Policy